Grain sorghum silage vs. forage sorghum silage; dehydrated alfalfa vs. Vitamin A, and the value of Aureomycin in cattle rations - Richardson, D.; Smith, E.F.; Koch, B.A.; Boren, Fred W. (Kansas Agricultural Experiment Station, 2011)
Two types of sorghum silage were used in this test. They were (1) DeKalb forage type which produced approximately 100 bushels of grain and 20 tons of silage per acre; and (2) RS610 grain type which produced approximately 75 bushels of grain and 10 tons of silage per acre. Forty Hereford heifer calves were divided into four lots of 10 each. Three lots received the grain sorghum silage and one the forage silage plus 2 pounds of grain. This was an attempt to keep the grain intake equal in all lots; however, since the forage sorghum produced so much grain, this lot may have received slightly more grain than others. Dehydrated alfalfa as a source of vitamin A was compared with vitamin A and with vitamin A plus Aureomycin.
Keywords: Beef; Grain sorghum silage; Forage sorghum silage; Dehydrated alfalfa; Vitamin A; Aureomycin